An analysis of a packed bed thermal energy storage system using sensible heat and phase change materials. (December 2019) - Yang, Xiaoping; Cai, Zhuodi
Highlights: Numerical and experimental study were performed to provide insight into the thermal behavior. The comparative analyses of sensible heat storage and phase change thermal storage were provided. The maximum temperature difference of the SHM appeared in the middle of the thermocline. Total storage charging time was reduced with the decrease of the melting point and latent heat. Abstract: Thermal energy storage is an important subsystem of a solar thermal power station. Compared with the two-tank storage system, the packed bed storage system uses a single tank to store thermal energy temporarily and release it when the energy is needed. The temperature distribution in the packed bed is generally in the form of the thermocline. This study analyzed a thermocline storage system packed with sensible heat material and phase change material. These materials were characterized separately in terms of temperature difference, outlet temperature profile, total energy storage, and charging time. Results demonstrated the presence of a maximum temperature difference in the middle of the thermocline. The maximum value of the temperature difference decreased following an increase in the charging time. The density and conductivity of the sensible material and the inlet velocity of the fluid considerably affected the temperature difference. In the phase-change thermal storage system, the temperature difference between the material and the fluid exhibited two peaks, wherein the first peak was higher than the second peak. The total storage charging time and storage energy increased following an increase in latent heat. The total storage charging time was reduced following a decrease in melting point, although the final thermal energy storage remained the same.